Bitcoin Risk Perception and Investment Behavior: The Role of Literacy and Trust - I Made Ardita; Ni Made Suci; Fridayana Yudiatmaja (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the effect of Bitcoin risk perception on stock investment decisions by considering the mediating roles of financial literacy and investor trust. The rapid development of digital financial technology, particularly cryptocurrencies, has introduced new dimensions of risk that influence investor behavior across financial instruments. This research adopts a quantitative approach with an explanatory design, involving 120 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Bitcoin risk perception has a positive and significant effect on financial literacy, investor trust, and stock investment decisions. Furthermore, financial literacy and investor trust significantly influence stock investment decisions and serve as partial mediators in the relationship between Bitcoin risk perception and investment decisions. These findings suggest that higher awareness of cryptocurrency risk encourages individuals to enhance their financial understanding and develop rational trust, ultimately leading to more informed investment decisions in the stock market. This study contributes to the integration of behavioral finance and financial technology by highlighting the indirect mechanisms through which risk perception shapes investment behavior. Practically, the results emphasize the importance of financial education and transparent information in improving investor decision-making in the digital era.